THE EFFECT OF PERCEIVED PERFORMANCE EXCELLENCE AND SATISFACTION TO CUSTOMER LOYALTY (EMPIRICAL STUDY ON MIXUE ICE CREAM AND TEA CUSTOMERS IN SURAKARTA) - Setyawan, Ridwan; Setyawan, Anton Agus (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2023)
This empirical study aims to investigate the relationship between perceived performance excellence, customer satisfaction, and customer loyalty in the specific context of Mixue Ice Cream and Tea customers. By examining these factors, the research seeks to providing perspectives on the factors that influence loyalty to customers and making practical advice for improving customer retention and overall business performance. This is a quantitative study that employs a survey method, using a non-probability sampling technique and also the method of purposive sampling. Researchers carry out descriptive analysis and use the partial least squares (PLS) to analyze data in this study. PLS is a component or variation-based structural equation modeling (SEM) model. Based on the values given to Cronbach's alpha and rho_A it was found that not all variables are considered reliable. All variables were found to be reliable, based on the composite reliability and AVE results. The results of hypothesis testing show that the entire hypothesis is acceptable and has a significant influence on each variable. Perceived performance excellence has been proven to have a positive and significant effect on customer satisfaction. Similarly to the influence of customer satisfaction on loyalty, perceived performance excellence on loyalty has a positive and significant influence. For further research, it is hoped that the researcher can add other variables and utilize variable indicator that has a low level of similarity.